Spectrophotometric Determination of Palladium(II) Ions Using a New Reagent: 4-(N’-(4-Imino-2-oxo-thiazolidine-5-ylidene)-hydrazino)-benzoic Acid (p-ITYBA) - Oleksandr S. Tymoshuk; Orest S. Fedyshyn; Lesia V. Oleksiv; Petro V. Rydchuk; Vasyl S. Matiychuk (Journal of Chemistry)
The simple, rapid spectrophotometric method for palladium(II) ions determination using a new analytical reagent is described. The interaction of Pd(II) ions with a reagent, of the class of azolidones, 4-(N′-(4-imino-2-oxo-thiazolidine-5-ylidene)-hydrazino)-benzoic acid, in water medium results in the formation of a complex. The Pd(II)-p-ITYBA complex shows maximum absorbance at a wavelength of 450 nm. The molar absorptivity is 4.30 × 103 L·mol−1·cm−1. The optimal pH for complex formation is 7.0. The developed method has a wide linearity range of 0.64–10.64 µg·mL−1 for Pd(II). The detection limit is 0.23 µg·mL−1. It was found that Co(II), Ni(II), Zn(II), Fe(III), Cu(II), Al(III), and many anions do not interfere with the Pd(II) determination. The proposed method was tested in the analysis of model solutions and successfully applied for the determination of palladium in catalyst. The obtained results show that this method can be used for serial determinations of palladium in various objects.